Analisis Motivasi Rasional dan Emosional terhadap Pengambilan Keputusan Pemilihan Partai Politik PKB Dapil 4 Kota Bandung melalui Konstruksi Image - Zauharudin, Jejen; Dagustani, Dani (Banking & Management Review, 2020)
Politics is always interesting to talk about no matter how complicated and chaotic political life is, everyone wants to know about political developments. Even rural people and housewives are increasingly fond of talking about politics, in accordance with their respective portions. Then the purpose of this study is to find out how the political marketing process is seen from the influence of rational motivation, emotional motivation on the decision of the PKB party election in 4 districts of Bandung through image construction. The methodological approach in this study is quantitative with a path analysis technique approach to discuss the direct effect of rational motivation, emotional motivation on imaged construction and also the direct effect on selection decisions as endogenous variables. The results show that the simultaneous influence of rational and emotional motivation significantly influences the construction of the image also simultaneously influences the decision of the PKB party election in 4 districts of Bandung. Partially significant rational motivation has an influence on image construction but emotional motivation has no significant effect on image construction. And partially, rational and emotional motivation significantly influence the decision of the PKB party election in 4 districts of Bandung. This study provides a small insight into the influence of rational motivation, emotional motivation on PKB party election decisions in the 4 districts of Bandung through image construction through descriptive and verification analysis with path analysis techniques. Keywords: Rational Motivation, Emotional Motivation, Election Decision Making, and Image Construction.